2005
DOI: 10.1124/mol.105.012351
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Thr139 in the Human Immunodeficiency Virus Type 1 Reverse Transcriptase Sensitivity to (+)-Calanolide A

Abstract: The coumarins represent a unique class of non-nucleoside reverse transcriptase inhibitors (NNRTIs) that were isolated from tropical plants. (ϩ)-Calanolide A, the most potent compound of this class, selects for the T139I resistance mutation in HIV-1 reverse transcriptase (RT). Seven RTs mutated at amino acid position 139 (Ala, Lys, Tyr, Asp, Ile, Ser, and Gln) were constructed by site-directed mutagenesis. The mutant T139Q enzyme retained full catalytic activity compared with wild-type RT, whereas the mutant T1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 31 publications
3
16
1
Order By: Relevance
“…This is contrary to recent reports using recombinant RT showing that, with the exception of T139A, which causes two-to threefold resistance to NNRTI, alanine substitution of residues 137, 139 and 140 does not influence drug susceptibility. 5,40 Our experiments do not rule out the possibility that mutations in the β7-β8 loop contribute to resistance if combined with known drugresistance mutations.…”
Section: Discussionmentioning
confidence: 89%
“…This is contrary to recent reports using recombinant RT showing that, with the exception of T139A, which causes two-to threefold resistance to NNRTI, alanine substitution of residues 137, 139 and 140 does not influence drug susceptibility. 5,40 Our experiments do not rule out the possibility that mutations in the β7-β8 loop contribute to resistance if combined with known drugresistance mutations.…”
Section: Discussionmentioning
confidence: 89%
“…5A, B, and C), whereas the interaction with the p51 subunit was primarily via the ␤7-␤8 loop, similar to (ϩ)-calanolide A (Fig. 5D) (2). The ␤7-␤8 loop (residues 132 to 140) of the p51 but not the p66 subunit is located at the RT heterodimer interface and contributes to the formation and stability of the NNRTI binding pocket (NNRTI) (18).…”
Section: Discussionmentioning
confidence: 99%
“…The ␤7-␤8 loop (residues 132 to 140) of the p51 but not the p66 subunit is located at the RT heterodimer interface and contributes to the formation and stability of the NNRTI binding pocket (NNRTI) (18). For instance, residues I132, I135, N136, E138, and T139 in the p51 subunit contributed specifically to NNRTI resistance (2,5,39). Moreover, previous data generated with the recombinant subunit-specific RT systems suggested that residue 139 in the p66 subunit is not involved in resistance to the F18 analogue (ϩ)-calanolide A (2, 6, 9).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports on the mechanism of TSAO resistance and structural modeling have suggested an influence of TSAO on RT dimerization, which places this compound in a unique position among the NNRTIs (SluisCremer et al, 2000 [90]; Rodriguez-Barrios et al, 2001 [86]. Auwerx et al [1] constructed seven different recombinant RT enzymes bearing a mutation at position 139 of RT and determined their catalytic activity as well as their resistance profiles against a variety of NNRTIs, including (+)-calanolide A and TSAO. The data obtained provided a rationale for the finding that it is the T139I mutation and not any other substitution at position 139 of HIV-1 RT that emerges under (+)-calanolide A pressure in cell culture.…”
Section: Mechanism Of Inhibition Of Rt Activitymentioning
confidence: 99%
“…Enzyme inhibition with respect to template-primer was uncompetitive with a Ki of 26 nM. Reverse transcriptase enzymes containing point mutations in which tyrosine 181 was changed to either cysteine or isoleucine exhibited marginal resistance to inophyllums but were resistant to (+)-(5S)-4,5,6,7-tetrahydro-9-chloro-5-methyl-6-(3-methyl-2-butenyl)-imidazo[4,5,1-j,k] [1,4]benzodiazepin-2-(1H)-thione. Inhibition of avian myeloblastosis virus reverse transcriptase and Moloney murine leukemia virus reverse transcriptase by inophyllum B was detectible, suggesting that these inhibitors may be more promiscuous than other previously described nonnucleoside inhibitors.…”
Section: Inophyllumsmentioning
confidence: 99%